Supply Chain Risk of Animal Welfare, Halal, and Food Safety at RPH Jatimulya and Kranji Market in Bekasi City - Makarim, Alwi Salam; Jahroh, Siti; Ramadyanto, Widodo (Business Review and Case Studies, 2024)
Risk management was needed to minimize economic loss due to risks related to animal welfare, halal, and food safety and was necessary for sustainable business development. This study identified risk factors and agents, analyzed risk impacts, and determined the effectiveness of mitigation strategies in their application to risk agents related to animal welfare, halalness, and safety at the Jatimulya abattoir and Kranji market meat retailers in the same supply chain of the beef industry in Bekasi City using the 2-Phase House of Risk (HOR) method. The results showed that there were 14 risk events caused by 16 risk agents at Jatimulya abattoir and 7 risk events caused by 11 risk agents at Kranji market beef retailers. The risk agents that had the potential to cause the largest risk events at RPH Jatimulya were bruises on cattle (A1), knives and tools not being sterilized before use (A8), and the absence of a cooler for storing meat after slaughter (A14). As for retail traders in Kranji market, the hands of sellers and buyers were not sterile (A18), knives and tools were not sterilized (A20), and meat storage in the freezer was mixed with other goods (A25). Priority risk mitigation strategies for Jatimulya abattoir were adjustment of overcrowded pen capacity (PA2), creating SOPs for the use of tools and making a place to sterilize tools (PA4), and renting cold storage (PA7). Meanwhile, the Kranji market beef retailers provided rubber gloves for buyers (PA9), created SOPs for the use of tools and the creation of tool sterilizers (PA12), and provided special refrigerators to store meat products (PA14). Keywords: risk management, beef, animal welfare, halal, food safety